UI testing with the UIAutomation framework - Pilone, Dan (O'Reilly breakdown., 2010)
"In this Breakdown, Dan Pilone introduces and demonstrates the UIAutomation framework, which allows for robust testing of your app's user interface. You'll learn how to ensure your keyboards and swipes and text boxes all behave, and quickly impress your users with a flexible and responsive user interface."--Resource description page.